Synergistic and Antagonistic Effects of Mixed-Leaf Litter Decomposition on Nutrient Cycling - Vestine Mukamparirwa; Salim M. S. Maliondo; Canisius Patrick Mugunga (Plants)
Understanding decomposition patterns of mixed-leaf litter from agroforestry species is crucial, as leaf litter in ecosystems naturally occurs as mixtures rather than as separate individual species. We hypothesized that litter mixtures with larger trait divergence would lead to faster mass loss and more balanced nutrient release compared to single-species litter. Specifically, we expected mixtures containing nutrient-rich species to exhibit synergistic effects, resulting in faster decay rates and sustained nutrient release, while mixtures with nutrient-poor species would demonstrate antagonistic effects, slowing decomposition. We conducted a mesocosm experiment using a custom wooden setup filled with soil, and the litterbag method was used to test various leaf litter mixtures. The study involved leaf litter from six agroforestry tree species: three species from humid highland regions and three from semi-arid regions. Treatments included three single-species leaf litter mixtures, three two-species mixtures, and one three-species mixture, based on the sampling region. Species included Calliandra calothyrsus (Ca), Croton megalocarpus (Cr), Grevillea robusta (G), Alnus acuminata (A), Markhamia lutea (M), and Eucalyptus globulus (E). Decay rate constants (k) were estimated using non-linear least-squares regression and observed mass loss was compared to predicted values for mixed-species litter treatments to assess synergistic and antagonistic effects. A two-way linear mixed-effects model was employed to explain variation in mass loss. Results indicate positive non-additive effects for leaf litter mixtures including nutrient-rich species and negative non-additive effects for mixtures including nutrient-poor species. The mixture of Ca + Cr + G had positive non-additive or synergistic effects as it decomposed faster than its corresponding single-species litter. Leaf litters with higher lignin content, such as A + M + E and Ca + Cr + G, exhibited less lignin release compared to what would be expected based on individual litter types, demonstrating antagonistic effects. These findings highlight that both litter nutrient constituents and litter diversity play an important role in decomposition processes and therefore in the restoration of the degraded and nutrient-depleted soils of Rwanda.